2005
DOI: 10.1038/nature04230
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the 1918 influenza virus polymerase genes

Abstract: The influenza A viral heterotrimeric polymerase complex (PA, PB1, PB2) is known to be involved in many aspects of viral replication and to interact with host factors, thereby having a role in host specificity. The polymerase protein sequences from the 1918 human influenza virus differ from avian consensus sequences at only a small number of amino acids, consistent with the hypothesis that they were derived from an avian source shortly before the pandemic. However, when compared to avian sequences, the nucleoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
685
1
25

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 942 publications
(718 citation statements)
references
References 30 publications
7
685
1
25
Order By: Relevance
“…Association between a few mutations/genes and dramatic phenotypic changes or fitness improvement have been reported in prokaryotes, eukaryotes and viruses (Taubenberger et al, 2005;Wang et al, 2005;Zeyl 2005;Herring et al, 2006;Schoustra et al, 2009). Results from this study indicated the linkage between significantly increased salt tolerance and a few mutations.…”
Section: Discussionmentioning
confidence: 52%
“…Association between a few mutations/genes and dramatic phenotypic changes or fitness improvement have been reported in prokaryotes, eukaryotes and viruses (Taubenberger et al, 2005;Wang et al, 2005;Zeyl 2005;Herring et al, 2006;Schoustra et al, 2009). Results from this study indicated the linkage between significantly increased salt tolerance and a few mutations.…”
Section: Discussionmentioning
confidence: 52%
“…Research 15,16 Research describes reconstruction of the lethal 1918 pandemic virus, concludes that this virus was entirely avian, and finds some similarities with H5N1.…”
Section: Oct 2005mentioning
confidence: 99%
“…15 May 2010 FAO reports that, during March 2010, the overall HPAI incidence in Indonesia based on PDSR village-level surveillance was 1.5 newly found infected villages per 1000 villages in the coverage area, with incidence rates varying widely among provinces. Incidence rates were highest in Kepulauan Bangka Belitung, Yogyakarta, Lampung, and Jambi provinces.…”
Section: May 2010mentioning
confidence: 99%
“…Los estudios virológicos actuales han probado que este virus era enteramente nuevo para los seres humanos y se ha sugerido que su origen pudo haber sido aviar 19 . Las epidemias de 1957, 1968 y 1977 estaban todas relacionadas directamente con esa primera epidemia y consistían en los virus que experimentaron la deriva genética/antigénica: H1N1, H2N2 o el reajuste H3N2, y todos ellos se han encontrado desde entonces en pájaros en Asia 20 .…”
Section: Reconocimiento Histórico De La Gripe Y De La Gripe Aviarunclassified